1995
DOI: 10.1007/bf00037681
|View full text |Cite
|
Sign up to set email alerts
|

Effects of inhibitors of polyamine biosynthesis and of polyamines on strawberry microcutting growth and development

Abstract: The primary free polyamines identified during growth and development of strawberry (Fragaria x ananassa Duch.) microcuttings cultivated in vitro were putrescine, spermidine and spermine. Polyamine composition differed according to tissue and stages of development; putrescine was predominant in aerial green tissues and roots, a-DL-difluoromethylarginine (DFMA), a specific and irreversible inhibitor of the putrescine-synthesizing enzyme, arginine decarboxylase (ADC), strongly inhibited growth and development. Ap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
6

Year Published

1999
1999
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(13 citation statements)
references
References 20 publications
0
7
0
6
Order By: Relevance
“…Treatments with the other two PAs, spermidine and spermine, caused no response except at the highest tested concentration and produced a lower number of roots. Tarenghi et al (1995), Nag et al (1999), and Tang and Newton (2005) reported the promotive role of spermidine and putrescine on root elongation and growth from stem cuttings of Vigna radiata, Fragaria microcuttings, and regenerated Virginia pine plantlets, respectively. A number of unrelated dicotyledonous species, such as Nicotiana tabacum, Phaseolus vulgaris, Vitis vinifera, Arabidopsis thaliana, and Pringlea antiscorbutica also share common features of PA involvement in root development (Couee et al 2004).…”
Section: Resultsmentioning
confidence: 96%
“…Treatments with the other two PAs, spermidine and spermine, caused no response except at the highest tested concentration and produced a lower number of roots. Tarenghi et al (1995), Nag et al (1999), and Tang and Newton (2005) reported the promotive role of spermidine and putrescine on root elongation and growth from stem cuttings of Vigna radiata, Fragaria microcuttings, and regenerated Virginia pine plantlets, respectively. A number of unrelated dicotyledonous species, such as Nicotiana tabacum, Phaseolus vulgaris, Vitis vinifera, Arabidopsis thaliana, and Pringlea antiscorbutica also share common features of PA involvement in root development (Couee et al 2004).…”
Section: Resultsmentioning
confidence: 96%
“…It has been reported that the inhibition Trees (2010) 24:975-992 977 of polyamine synthesis blocks the mitotic cell cycle by blocking the transition between G1 and S phase where increased levels of spermidine and spermine have been found (Couée et al 2004). Both Martin-Tanguy and Carré (1993) and Tarenghi et al (1995) hypothesized that the endogenous concentrations of polyamines might be growth limiting based on observations of the developmental stimulation of higher plants. A direct relationship between high polyamine content, such as putrescine and spermine, and the onset of ARF has been demonstrated, which accentuates the possible participation of these substances in the general cellular processes of division and differentiation in the rooting process (Couée et al 2004;MartinezPastur et al 2007).…”
Section: Polyaminesmentioning
confidence: 99%
“…For example, treatment with D-Arginine (D-Arg), a specific ADC1/2 competitive inhibitor, leads to a reduction in Put and a longer primary root length in Pringlea antiscorbutica [ 15 ]; perturbation of Put biosynthesis in adc1 and adc2 single T-DNA mutants shows no root phenotype, whereas the double mutant is lethal [ 20 ]; mutation in BUD2 gene, which encodes S-adenosylmethionine decarboxylase 4 (SAMDC4), a key enzyme required for PA biosynthesis in A. thaliana , resulted in Put accumulation and altered root architecture [ 21 ]; silencing both ADC1 and ADC2 shows a significant reduction in primary root length [ 18 ], and high levels of Put treatment exhibit a similar phenotype in Arabidopsis [ 22 ]. Exogenous application of low levels of Put has no effect on root growth in Arabidopsis [ 23 , 24 ], but treatment with 1 mM Put increases root length in strawberries [ 25 ]. Treatment with an inhibitor of Tspm biosynthesis increased primary root growth, whereas treatment with exogenous Tspm inhibited root growth [ 26 ]; and inhibition or induction of Arabidopsis polyamine oxidase 5 (AtPAO5) significantly affected root length and development [ 27 ].…”
Section: Introductionmentioning
confidence: 99%